2023
DOI: 10.1186/s41232-023-00274-6
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles from immortalized mesenchymal stromal cells protect against neonatal hypoxic-ischemic brain injury

Abstract: Background Human mesenchymal stromal cell (MSC)-derived extracellular vesicles (EV) revealed neuroprotective potentials in various brain injury models, including neonatal encephalopathy caused by hypoxia–ischemia (HI). However, for clinical translation of an MSC-EV therapy, scaled manufacturing strategies are required, which is challenging with primary MSCs due to inter- and intra-donor heterogeneities. Therefore, we established a clonally expanded and immortalized human MSC line (ciMSC) and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 93 publications
1
4
0
Order By: Relevance
“…First, we showed that HI reduced cell proliferation in the SGZ: this effect has been previously described [ 39 , 40 ], whereas others have shown either no differences in the number of proliferating cells between HI and sham-operated animals [ 41 ] or increased [ 42 ] total counts of new cells after HI. The treatment with 2-AG increased the number of Ki67+ proliferating cells in both the whole hippocampus and the SGZ when compared to non-treated HI animals.…”
Section: Discussionsupporting
confidence: 68%
“…First, we showed that HI reduced cell proliferation in the SGZ: this effect has been previously described [ 39 , 40 ], whereas others have shown either no differences in the number of proliferating cells between HI and sham-operated animals [ 41 ] or increased [ 42 ] total counts of new cells after HI. The treatment with 2-AG increased the number of Ki67+ proliferating cells in both the whole hippocampus and the SGZ when compared to non-treated HI animals.…”
Section: Discussionsupporting
confidence: 68%
“…To this end, we decided to immortalize MSCs and try to expanded them at the clonal level. Indeed, as described recently, we have successfully established this method and have expanded the first monoclonal cell lines for fare more than 100 population doublings without observing any indication of senescence, thus, clearly overcoming the Hayflick’s limit ( Labusek et al, 2023 ). Notably, being expanded in appropriate media, some of these clonal immortalized MSC (ciMSC) lines repetitively allowed the preparation of EV products with confirmed in vitro immunomodulatory properties, while EV products of other ciMSC lines for now always failed to show such activities.…”
Section: Discussionmentioning
confidence: 89%
“…Combined to our specific interest in establishing novel treatment strategies for perinatal brain injuries ( Jensen, 2023 ), ciMSC-EVs were administered to a murine model of neonatal hypoxia induced encephalopathy. The ciMSC-EV application significantly suppressed the disease symptoms at various cellular levels implying a multimodal mode of action that can hardly be mimicked by monomolecular compounds ( Labusek et al, 2023 ). Thus, even though we cannot exclude that appropriate production strategies might overcome some of the discussed heterogeneity issues, we consider future MSC-EV therapeutics will derive from monoclonal MSC lines.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also demonstrated in vitro using the HL-1 cardiomyocyte line that the protective effect of these exosomes is associated with the activation of the gp130/JAK signaling pathway [ 97 ]. In a recent paper by Labusek et al, exosomes derived from immortalized MSCs are shown to have similar neuroprotective capacity as exosomes from primary MSCs in a mouse model of neonatal hypoxic-ischemic brain injury [ 98 ]. An article by Zhang et al shows a positive effect of topically applied exosomes derived from E1-MYC-immortalized human MSCs in a mouse imiquimod-induced psoriasis model [ 99 ].…”
Section: Immortalized Cells As Producersmentioning
confidence: 99%